Основні вимоги до нового покоління вітчизняних магістральних електровозів для вантажної і пасажирської поїздної роботи - Панасенко, Надія Миколаївна (НТУ "ХПІ", 2005)
Розглянуті основні вимоги до нового покоління вантажно-пасажирських електровозів для залізниць України і вигоди від реалізації цих вимог.

The basic requirements for a new generation of freight-and-passenger electric locomotives intended for the railways in Ukraine are considered, gain due to implementation of these requirements estimated.
The basic requirements for newgeneration domestic mainline electric locomotives for freight train and passenger trains
Keywords: вантажно-пасажирські електровози; залізничний транспорт; локомотиви; залізничний рух України; електричний транспорт; тепловозобудування; electric railways; electric traction system; semiconductor converter; electric stock; asynchronous electric motor; actuating shaft